The social construction of 'many Kurdishnesses': Mapping sub-identities of 'EU-ising' Kurdish politics. (October 2019) - Tekdemir, Omer
Political identity is a central issue in Kurdish rights' demands in Turkey. However, Kurdish political identity is not formed in a homogeneous context and has become a ground for a hegemonic struggle between internal groups such as Kurdish leftist/secularists, Kurdish Islamist/conservatives and Kurdish pragmatist/opportunists ('white Kurds'). The study critically analyses the scope of mainstream Kurdishness and its different sub-identities as the representatives of these subaltern groups seek to deepen Kurdish democratisation and widen public space in a new agonistic articulation. This paper addresses the emergence of a new political identity in the restoration of Kurdishness and radical pluralism by employing a poststructuralist methodology. Moreover, it suggests a new collective will, the 'EU-ising of Kurdishness', socially constructed by 'many Kurds' through the development of a new political grammar and discursive practice. The new superstructure as a nodal point entails the radical plural democratisation of contemporary Kurdish society relative to the principles of liberty and equality.